Development of a Javanese Script Learning Website Based on Experiential Learning and Audio Instructional to Enhance Javanese Script Grapheme Literacy of Visually Impaired Children - Risywan Taufiq; Nur Hanifah Insani; Mujimin Mujimin (Institute of Multidisciplinary Research and Community Service, 2026)
The fostering of Javanese script literacy should be implemented across all levels of Javanese society, including visually impaired children, as part of an inclusive effort to preserve cultural heritage. However, the limited availability of accessible learning media remains a major challenge in Javanese script instruction. Therefore, this study aims to develop an audio-instruction-based learning website for visually impaired students, integrated with the experiential learning model and packaged as a game-based challenge called Bagong’s Smart, to introduce and train students in writing complete and accurate Javanese script graphemes. This study employed the Four-D (4D) development model, consisting of the define, design, develop, and disseminate stages. Website development was carried out using PHP and the Laravel framework in Visual Studio Code. The Javanese script font used was Mbata Sarimbag, which has been shown to help visually impaired students more easily recognize and map grapheme patterns in Javanese script. The research was conducted at SLB Negeri Semarang using observation, interviews, and questionnaires as data collection techniques. Data analysis was carried out through media feasibility testing, Javanese script material feasibility testing, and evaluation of the media’s potential to support learning. The results indicate that Bagong’s Smart is highly feasible for use in learning the Javanese script by students with disabilities. This feasibility is supported by the media validation results, which achieved an average score of 91.1%, and the material validation results, which reached an average score of 97.3%. In addition, the Bagong’s Smart website demonstrated the potential to support visually impaired students’ ability to write complete and accurate Javanese script graphemes, as evidenced by the average score for students’ independent Javanese script writing, which reached 81.9%. This study offers an alternative website-based digital learning platform that optimizes audio instructional features and direct learning experiences to expand educational accessibility for visually impaired students. Keywords: Experiential learning, Javanese script grapheme, visual impairment, web accessibility.